Microbiological Quality of Some Milky Sweets Offered for Consumption in the City Center of Konya and Manufactured Experimentally - SECIM, Yilmaz; UCAR, Gurkan (Pakistan Journal of Nutrition, 2013)
Eighty units milky desserts consumed in Konya and experimentally produced milky desserts have been analyzed in terms of total aerobic mesophilic microorganisms coliform group of microorganisms, yeast and mold and Staphylococcus aureus. The average values of the total number of aerobic mesophilic microorganisms coliform group of microorganisms, yeast and mold and Staphylococcus aureus of milky desserts sold in the market has been determined to have been respectively between log10 2.17-3.44, 0.66-3.23, 1.03-2.08 and 0.87-3.76. The values of milky desserts produced experimentally have been determined, respectively between log10 0-1.00, 0.82-1.74, 0-3.34, 0-0.98 of the milky dessert samples of 80 units it has been determined total aerobic mesophilic microorganisms in 59 samples (73.75%), coliform organisms in 46 samples (57.50%), yeast and mold in 37 samples (46.25%) and Staphylococcus aureus in 47 samples (58.75%). Microbiological values of experimentally produced milky dessert samples have been found to have been quite lower than the ones produced in the market. It has been found important differences in the values of the total number of aerobic mesophilic microorganisms coliform group of microorganisms, yeast and mold and Staphylococcus aureus of milky desserts consumed in market and produced experimentally. It has been appeared to be necessary the effective and continuous control of production and selling areas of milky desserts. Also it has been appeared to be necessary to obey the hygiene rules in production and selling areas of milky desserts.